Factors that influence tourists' satisfaction in China; evidence from selected tourist destinations in Nanjing city - Shajedul, Islam; Abdul, Ba (Technium Social Sciences Journal, 2022)
Tourism is a growing industry around the world. The tourism industry plays a significant role in the economy of developing and developed countries. This study aims to understand the factors that influence tourists' satisfaction with selected tourism destinations in Nanjing city. This study collected data from 100 random visitors' by designing a survey questionnaire. For data collection, a simple random sampling method was applied. For analyzing data, frequency analysis and descriptive statistics were employed. Results of the study show that product, Price, and place are the vital factors that significantly affect tourists' satisfaction. Therefore, Empirical evidence suggests that all the related parties such as tourists, the tourism industry, and local government authorities can use this study to know the factors that influence tourists' satisfaction. In addition, this study can also help businesses understand tourists' satisfaction factors and advance along with tourism destinations' products offered to prospective tourists.